Cyclosporine and Extracorporeal Photopheresis are Equipotent in Treating Severe Atopic Dermatitis: A Randomized Cross-Over Study Comparing Two Efficient Treatment Modalities - Koppelhus, Uffe; Poulsen, Johan; Grunnet, Niels; Deleuran, Mette Søndergaard; Obitz, Erik (Frontiers in Medicine, 2014)
Background Severe atopic dermatitis (AD) is a recurrent and debilitating disease often requiring systemic immunosuppressive treatment. The efficacy of cyclosporine A (CsA) is well proven but potential side effects are concerning. Several reports point at extracorporeal photopheresis (ECP) as an alternative treatment modality with few and mild side effects. However, no direct comparison between CsA and ECP in the treatment of AD has been performed so far. Objectives. To compare the efficacy of CsA (3 mg/kg/day) and ECP (administered two consecutive days twice a month) in a cohort of patients with severe AD. Methods A randomized cross-over study involving twenty patients with severe AD (SCORAD index 41-89) refractory to other treatments. The patients were allocated to a 4 month course of either of the two treatment modalities. Individual relapse periods (2-8 weeks) were interspersed before cross-over to the other treatment modality. Treatment efficacy was evaluated by SCORAD, PRURITUS (VAS-index 0-10), ”overall global assessment” and serological biomarkers; sIL-2Rα, sE-selectin, eosinophilocytes, basophilocytes and sIgE. Results 15 patients completed treatment. Both treatments lead to a marked and significant decrease in SCORAD and pruritus index. The average reduction of the SCORAD and pruritus index, respectively was a little higher for ECP treatment compared to CsA treatment, however the differences did not reach statistical significance. The ”overall global assessment” was significantly higher in patients who underwent ECP therapy as compared to CsA treatment. None of the biomarkers showed significant changes after either treatment when compared to the initial values. Conclusion ECP administered on two consecutive days twice a month to patients with severe AD has similar potency as CsA administered daily in a moderate dose. ECP is a treatment alternative in patients with severe AD that do not tolerate or are refractory to conventional immunosuppressants.